An Assessment of Australian Research Library Journal Cancellations, 1990-2003 - Genoni, Paul (Australian Library and Information Association, 2005)
This paper reports on the outcomes of research assessing the nature and extent of print journal cancellations by Australian research libraries since 1990. The cancellation activity of two groups of libraries, one representing the national and state library sector and the other the university library sector, was examined. These two groups were tested for their cancellation of both Australian and international journals. From the results some conclusions are reached about the factors driving the cancellations and the implications these cancellations might have for the nation's access to scholarly journal literature.